LEXICAL METAPHORICAL REPRESENTATION OF DOCTORS AND PATIENTS IN MEDICAL INTERACTIONS - EZEUGO , Toochukwu John; CHUKWU , Ephraim A. (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
Previous studies explore patients' metaphorical descriptions of illness and doctors’ mechanistic explanations. Lexical metaphors are not only used to present disease or treatment options in medical consultations, but also to conceptualise doctors and patients, and their roles in clinical settings. Participants in medical encounters rarely know how they are perceived and construed by their co-interlocutors. Drawing on Conceptual Metaphor Theory by Lakoff and Johnson (1980), this study conducts an exploratory quantitative analysis of the distribution of lexical metaphors in doctor-patient interactions at Alex Ekwueme Federal Teaching Hospital, Abakaliki. One hundred questionnaires are distributed; seventy valid responses are received—twenty-five from doctors and forty-five from patients. Results reveal metaphorical asymmetries: doctors view themselves as service providers, experts, helpers, or saviours, while patients additionally describe doctors as angels or, occasionally, enemies. Patients are framed as clients, helpless individuals, or the needy. These metaphorical frames reflect emotional versus professional orientations and underlying power dynamics in doctor–patient communication.